Secular trend of gestational diabetes mellitus and its interaction effect with advanced maternal age on adverse maternal-perinatal outcomes among primiparous singleton and twin pregnancies in Hubei, China (2011-2019) - Nawsherwan,; Shen, Hong-tao; Haq, Ijaz Ul; Nabi, Ghulam; Naeem, Shafaq; Xu, Jie-lian; Ni, Xiaoqiu (Frontiers in Endocrinology, 2025)
BackgroundGestational diabetes mellitus (GDM) is a metabolic disorder of pregnancy associated with multiple adverse maternal-perinatal outcomes among singleton and twin pregnancies and its incidence is increasing across the globe. We aimed to find the secular trend of GDM and its interaction effect with advanced maternal age (AMA) on adverse maternal-perinatal outcomes among primiparous singleton and twin pregnancies in Hubei, China.MethodsA retrospective-based cohort study was conducted at the Wuhan University Renmin Hospital, Hubei Province, China, between 2011 and 2019. A chi-square test was used to explore a significant difference in the adverse maternal-perinatal outcomes between younger (18–34 years) and older/AMA (≥35 years) women with singleton and twin gestations. A multiple binary logistic regression model was used to estimate the adverse effect of GDM on maternal-perinatal outcomes among younger and older women with singleton and twin gestations, taking non-GDM as a reference group. We used a joinpoint regression analysis to find the secular trend of GDM prevalence among singleton and twin pregnancies during the study period.ResultsThe secular trend of GDM [average annual percentage change (AAPC) 51.3% (95% confidence interval (95%CI): 3.9, 120.5)] significantly increased among singleton pregnant women. Based on age groups, the secular trend of GDM significantly increased in younger women with singleton [AAPC, 53.2% (95%CI: 2.0, 130.0)] and twin gestations [AAPC, 83.7% (95%CI: 36.0, 148.1)] between 2011 and 2019. Among younger women with singleton gestation, GDM showed a higher risk of hypertensive disorders of pregnancy (HDP), C-section, and macrosomia compared with non-GDM. Among younger women with twin gestations, GDM increased the risk of nuchal cord, polyhydramnios, and preterm births. GDM was associated with an increased risk of HDP, nuchal cord, macrosomia, and congenital defects among older women with singleton gestation. The interaction effect between GDM and AMA significantly increased the risk of HDP (adjusted odds ratio (aOR), 2.5; 95% CI: 1.8, 3.6), C-section (aOR, 2.5; 95% CI: 1.9, 3.4), and preterm birth (aOR, 1.5; 95% CI: 1.1, 1.9) among singleton pregnancies.ConclusionAmong younger women with singleton and twin gestations, the secular trend of GDM significantly increased between 2011 and 2019. Among singleton pregnancies, GDM is associated with an increased risk of several adverse maternal-perinatal outcomes in both younger and older women. The interaction effect between GDM and AMA significantly increased the risk of HDP, C-section, and preterm birth among singleton pregnancies.